Establishment of a tourist agency under the Law of the Republic of Serbia - Ilić Milica (Turističko Poslovanje, 2023)
The main bearers of legal affairs in the tourism industry are travel agencies. To sell its services, the travel agency enters into legal relations with its clients as well as with other travel agencies and organizations. It produces numerous legal consequences with its operations. Normative regulation of their establishment and business is necessary for legal certainty. The Law on Tourism of the Republic of Serbia precisely defines the procedure for establishing tourist agencies as well as the conditions that a tourist agency must fulfill if it wants to do business. At the same time, it should satisfy all the conditions in the business itself that arise from other legal acts related to business and the economy. This paper examines the establishment of travel agencies in the Republic of Serbia, by looking in detail at the procedure for establishing travel agencies, as well as the conditions they must fulfill, and attention is also paid to the specifics that arise in practice during their establishment.